2022
DOI: 10.1007/s10639-022-11032-5
|View full text |Cite
|
Sign up to set email alerts
|

A web-based survey of educational opportunities of medical professionals based on changes in conference design during the COVID-19 pandemic

Abstract: Owing to the coronavirus disease 2019 (COVID-19) pandemic, understanding how to hold future online academic conferences effectively is imperative. We assessed the impact of COVID-19 on academic conferences, including facilities and settings for attendance, participation status, cost burden, and preferences for future styles of holding conferences, through a web-based questionnaire survey of 2,739 Japanese medical professionals, from December 2020 to February 2021. Of the participants, 28% preferred web confere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Roffi et al have demonstrated that reducing barriers to entry by utilizing virtual access dramatically increases participant numbers, with a greater proportion of attendees who are younger, female, or from developing countries. This has been further emphasized in surveys demonstrating the explicit preference of participants toward virtual or hybrid style conferences over FTF …”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Roffi et al have demonstrated that reducing barriers to entry by utilizing virtual access dramatically increases participant numbers, with a greater proportion of attendees who are younger, female, or from developing countries. This has been further emphasized in surveys demonstrating the explicit preference of participants toward virtual or hybrid style conferences over FTF …”
mentioning
confidence: 96%
“…While participants often show a preference toward virtual meetings, researchers report a reluctance to submit academic abstracts to meetings that are held virtually, preferring FTF meetings . Maybe this is related to the opportunities to network and gain feedback from colleagues that may not be possible for a virtual meeting.…”
mentioning
confidence: 99%